2005
DOI: 10.1128/jcm.43.8.4129-4138.2005
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Outbreak of Infection Due to TEM-21-Producing Strains ofPseudomonas aeruginosaand Enterobacteria in a Nursing Home

Abstract: Over a 6-year period, 24 extended-spectrum ␤-lactamase (ESBL)-producing isolates of Pseudomonas aeruginosa were collected from 18 patients living in a nursing home. These isolates had a delayed development of a red pigment and exhibited a similar antibiotype (resistance to all ␤-lactams except for imipenem and to gentamicin, tobramycin, netilmicin, ciprofloxacin, and rifampin) associated with the production of the TEM-21 ␤-lactamase and a type II 3-N-aminoglycoside acetyltransferase [AAC(3)-II] enzyme. Surpris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Specific primers were used under standard PCR conditions to detect ESBL-and MBL-encoding genes, namely, bla TEM , bla SHV , bla CTX-M , bla GES , bla PER , bla VEB , bla BEL , bla KPC , bla IMP , bla VIM , bla SPM , bla GIM , and bla AIM (7,12,15,16,17,20,23,26,29,30,38,42). The genetic environment of bla IMP was determined by PCR using the previously published specific primers to anneal at the 5Ј and 3Ј conserved sequences (CSs) of class 1 integrons, followed by sequencing (24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific primers were used under standard PCR conditions to detect ESBL-and MBL-encoding genes, namely, bla TEM , bla SHV , bla CTX-M , bla GES , bla PER , bla VEB , bla BEL , bla KPC , bla IMP , bla VIM , bla SPM , bla GIM , and bla AIM (7,12,15,16,17,20,23,26,29,30,38,42). The genetic environment of bla IMP was determined by PCR using the previously published specific primers to anneal at the 5Ј and 3Ј conserved sequences (CSs) of class 1 integrons, followed by sequencing (24).…”
Section: Methodsmentioning
confidence: 99%
“…The ESBLs reported for P. aeruginosa are SHV, TEM, PER, VEB, BEL, GES, and, more recently, CTX-M types (1,7,8,16,20,23,29). The GES-type enzymes are unusual since point amino acid changes in their active sites may extend their hydrolytic activity to carbapenems (31,39,40).…”
mentioning
confidence: 99%
“…The differences measured for P. aeruginosa strains equate to a coding capacity for more than 500 proteins with an average size of 50 kilo Daltons (KD). Genomic plasticity via the acquisition of horizontally-transmitted genes has been associated with the evolution of epidemic strains for animals, plants, and humans among the P. aeruginosa [5][6][7]. Lewis et al identified and characterized a transmissible cystic fibrosis strain, designated at MA, which contains a unique pathogenicity island that includes 18 genes from two prophages and a cholera-toxin-like gene [8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, most of the 50 strains were resistant to aminoglycosides, including 24 that exhibited a TNt(A) phenotype (tobramycin, netilmicin, and low-level amikacin resistance) associated with an aac(6Ј)-I gene, 1 strain with a GTNt phenotype (gentamicin, tobramycin, and netilmicin resistance) related to an aac(3)-II gene, and 12 strains with the combined GTNtA phenotype and both enzyme-encoding genes, as verified by PCR amplifications (2,3,8,9). The strains also exhibited resistances to sulfonamides (78%), trimethoprim (74%), chloramphenicol (64%), and tetracycline (37%) ( Table 1).…”
mentioning
confidence: 99%